Impellent impeller—Switching intra‐aortic balloon pump to IMPELLA‐CP after ST‐segment elevation myocardial infarction and refractory cardiogenic shock. Issue 8 (19th June 2019) - Contarini, Marco; Costa, Francesco; Garcia Ruiz, Maria Victoria; Scalise, Renato F. M.; De Velli, Giovanni; Murè, Paola; Mazzone, Paolo; Sacchetta, Giorgio; Andò, Giuseppe
Abstract: Cardiogenic shock is a dreadful complication of myocardial infarction. Despite widespread use and availability, intra‐aortic balloon pump (IABP) does not reduce mortality nor improves outcomes. Advanced mechanical circulatory support with IMPELLA system can substantially support hemodynamics and improve short‐term prognosis in patients with myocardial infarction and cardiogenic shock. Abstract : Cardiogenic shock is a dreadful complication of myocardial infarction. Despite widespread use and availability, intra‐aortic balloon pump (IABP) does not reduce mortality nor improves outcomes. Advanced mechanical circulatory support with IMPELLA system can substantially support hemodynamics and improve short‐term prognosis in patients with myocardial infarction and cardiogenic shock.